2017
DOI: 10.2214/ajr.16.17610
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Spindle Cell Breast Lesions

Abstract: Spindle cell lesions of the breast exhibit characteristic features at mammography, ultrasound, and MRI. Although a definitive diagnosis of these lesions cannot be made with diagnostic imaging alone, knowledge of their characteristic imaging features can assist in refining the differential diagnosis and guiding appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Although its cytomorphological features are similar to those of MFB, fibromatosis mimics breast carcinoma radiologically and clinically. Nonetheless, cytopathologists should be aware that MFBs seldomly show ill‐defined borders radiologically 19‐21 . Nodular fasciitis, on the other hand, creates a noncalcified, spiculated mass and architectural distortion that are observable via mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Although its cytomorphological features are similar to those of MFB, fibromatosis mimics breast carcinoma radiologically and clinically. Nonetheless, cytopathologists should be aware that MFBs seldomly show ill‐defined borders radiologically 19‐21 . Nodular fasciitis, on the other hand, creates a noncalcified, spiculated mass and architectural distortion that are observable via mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Mammographically, it commonly appears as a well-circumscribed high density mass without calcification (Fig 2 .). On ultrasound, the mass has a homogenous hypo to hyperechoic appearance with minimal posterior shadowing [22]. Histologically, spindle cell breast lipomas are composed of bland spindle cells intermingled with mature adipocytes, and collagen bundles (Fig.…”
Section: Spindle Cell Lipomamentioning
confidence: 99%
“…7). A well-defined hypoechoic mass is typically seen on ultrasound with or without variable degree of posterior acoustic shadowing [22]. Varying degrees of collagen and adipose tissue are seen with histological features sometimes mimicking those of spindle cell carcinoma of the breast, which can lead to misdiagnosis [49].…”
Section: Myofibroblastomamentioning
confidence: 99%
“…Fibroadenoma and phyllodes tumor should firstly be included in the differential diagnosis due to the black septum and lobulated shape of the mass shown on contrast-enhanced MRI. Duman L et al (10) reported that fibroadenoma tended to be homogeneously enhanced and had a hypointense internal septum, while in this case, even with a hypointense septum, the mass showed rapid heterogeneous enhancement which made a fibroadenoma unlikely. Although phyllode tumors are frequently lobulated in shape-this is similar to the MRI findings in this case-the internal cystic areas were detected in the former.…”
Section: Discussionmentioning
confidence: 63%